KLASIFIKASI HABITAT BENTIK ATOL KALEDUPA TAMAN NASIONAL WAKATOBI DENGAN ALGORITMA SUPPORT VECTOR MACHINE - Setiawan, Alim; Siregar, Vincentius Paulus; Susilo, Setyo B.; Mardiastuti, Ani; Agus, Syamsul B. (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
Kaledupa Atoll is one of the areas designated as a marine protection zone and local use zone in Wakatobi National Park. Spatial information on the benthic habitat of Kaledupa Atoll is very limited so that this information is expected to be a support in strategies and efforts to conserve marine biodiversity. This study aims to map the benthic habitat of Kaledupa Atoll using a pixel-based and object-based guided classification method/OBIA with a support vector machine (SVM) algorithm. The data used is the Sentinel-2 satellite image with a spatial resolution of 10 x10 m which was acquired on November 4, 2019. Observations of benthic habitats were carried out directly at the study site by placing quadrant transects and taking points on the dominant or homogeneous habitat area. The transect used is 100 x 100 cm2. Image classification uses thematic layer input from field data. The results of the classification of benthic habitats are grouped into six classes. Based on the OBIA method, benthic habitats can be mapped with an accuracy rate of 78.1%, while the pixel-based classification has an overall accuracy of 61.8%. Classification of benthic habitats with the SVM algorithm using the OBIA method provides better information than the pixel-based method.